Estudio de factibilidad para el desarrollo e implementación de un sistema de facturación y control de inventarios, para la Farmacia Zoilita, de la Parroquia San Juan del cantón Puebloviejo - Ronquillo Acosta, Erika Maholy (2021)
The present feasibility analysis was carried out at the “Zoilita” pharmacy of the San Juan del Cantón Puebloviejo parish, which is dedicated to the sale of all kinds of medicines and personal care products. Based on the study carried out, certain drawbacks were identified in the processes carried out by the pharmacy, such as: shortcomings in the management and control of inventories, since the process of recording and storing information manually in a notebook takes its In addition, human errors may arise that would cause financial or material losses to the pharmacy, billing is carried out in the same way, causing dissatisfaction in customers due to the waiting time. As a possible solution to the problems encountered, the present feasibility study is proposed for the development and implementation of a billing and inventory control system that automates pharmacy processes, streamlines billing time, improves accounting management and control of inventories, in order to provide customers with a fast, efficient service that increases the profitability of the business.